From Casino Royale to Spectre: Daniel Craig's James Bond. Issue 1 (2nd January 2018) - Dodds, Klaus; Funnell, Lisa
Abstract: : This introduction highlights the four areas of inquiry addressed by contributors featured in this special issue of Journal of Popular Film and Television, "James Bond in the Daniel Craig Era": agencies, moods, places, and structures. It also acknowledges the place of the Daniel Craig era in relation to other serial film franchises like the Jason Bourne and Batman series.